Preexposure to heat stress attenuates sepsis-associated inflammation and cognitive decline in rats. (29th May 2022) - Jiang, Sufang; Bai, Long; Zhang, Xiaoxiao; Zhou, Xiaoyu; Liu, Ya
Highlights: Mild heat stress induced expression of HSP70. Preinduction of HSP70 increased the survival rate after sepsis. Preinduction of HSP70 attenuated sepsis-induced cognitive impairment. Preinduction of HSP70 inhibited sepsis-induced inflammatory cytokine, hippocampal injuries and activation of microglia. Preinduction of HSP70 inhibited sepsis-induced NF-κB activation. Abstract: Sepsis is a life-threatening organ dysfunction due to an infection, leading to cognitive impairments. Studies have shown that heat shock protein 70 (HSP70) exhibited a neuroprotective effect. In this study we used mild heat stress to induce expression of HSP70, aiming to detect the effect of HSP70 on neurocognitive deficits associated with sepsis and explored the underlying mechanisms. Male rats were exposed to 42℃ for 15 min. After 12 h, they were subjected to cecal ligation and puncture (CLP). HSP70 and brain-derived neurotrophic factor (BDNF) expression, and nuclear level of NF-κB p65 were detected by western blot. Levels of inflammatory cytokines in circulation and hippocampus were measured by ELISA and RT-PCR. Neuronal morphology and damage of hippocampal neurons were assessed by Hematoxylin-Eosin (HE) and Nissl stainings. Microglial activation was determined by immunohistochemistry. Finally, neurologic and cognitive functions were evaluated using neurobehavioral scoring and morris water maze (MWM) test. Mild heat stress increased survival rate of sepsis rats. Mild heat stress upregulated HSP70, inhibited nuclear level of NF-κB p65 in hippocampus. Mild heat stress could diminish IL-1β and TNF-α levels in circulation and hippocampus. Furthermore, mild heat stress was able to enhance expression of BDNF and alleviate cognitive impairment after sepsis. Overall, these results indicated that mild heat stress showed protective effects on sepsis-associated encephalopathy rat model, which may be associated with upregulation of HSP70 and inhibition of NF-κB pathway.